Cryptography using Multiple – Chaos. Issue 1 (March 2021) - Raja Kumar, R.; Pandian, R.; Prem Jacob, T.; Pravin, A.; Indumathi, P.
Abstract: Seemingly random, chaotic dynamic systems have state variables that move about in a non periodic, bounded fashion. The sensitivity to initial conditions of chaotic signals also holds an interesting pattern. A seemingly tiny change in the values of initial condition, can greatly affect the values of output. This means that the cross-correlation of two chaotic functions of same source is very low. This pattern of chaotic functions makes their use in the field of cryptography more interesting. A more complex version of chaos is the multiple-chaos, where two or more chaotic functions are used, enhances the security of the procedure. Additionally the dynamically varying look-up table, which is being transmitted along with the encrypted message, ensures high reliability in transmitting the data. Overall, this method ensures high security and high reliability in transmitting the data.